Sennacherib at the gates of Jerusalem : story, history and historiography - Kalimi, Isaac.; Richardson, Seth. (Culture and History of the Ancient Near East, 2014)
Sennacherib and his ill-fated siege of Jerusalem fascinated the ancient world. Twelve scholars-in Hebrew Bible, Assyriology, archaeology, Egyptology, Classics, Aramaic, Rabbinic and Christian literatures-examine how and why the Sennacherib story was told and re-told in more than a dozen cultures for over a thousand years. From Akkadian to Arabic, stories and legends about Sennacherib became the first vernacular tales of the imperial world. These essays address outstanding historical issues of the campaign and the sources, and press on to expose the stories' theological and cultural roles in inner-cultural dialogues, ethnic origin stories, and morality tales. This book is the first of its kind for readers seeking out historical and historiographic bridges between the ancient and late antique worlds. \'This work will undoubtedly serve as an important resource on the Assyrian attack on Jerusalem in 701...\' Song-Mi Suzie Park, Austin Presbyterian Theological Seminary, Horizons in Biblical Theology